2012
DOI: 10.1109/tit.2012.2205663
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Algorithm for Finding Dominant Trapping Sets of LDPC Codes

Abstract: This paper presents an efficient algorithm for finding the dominant trapping sets of a low-density parity-check (LDPC) code. The algorithm can be used to estimate the error floor of LDPC codes or to be used as a tool to design LDPC codes with low error floors. For regular codes, the algorithm is initiated with a set of short cycles as the input. For irregular codes, in addition to short cycles, variable nodes with low degree and cycles with low approximate cycle extrinsic message degree (ACE) are also used as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
112
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(115 citation statements)
references
References 40 publications
(110 reference statements)
2
112
0
1
Order By: Relevance
“…8(b) we present the performance of two longer codes, Margulis (2640, 1320) code and PEG (1008, 504) code, both (3, 6)-regular LDPC codes. Although the dominant trapping sets are not the same for these codes [30], for both codes the performance improvement can be observed if L ≥ 20. Allowing larger number of iterations results in additional performance improvement.…”
Section: Simulation Analysis Of the Finite Length Ldpc Codesmentioning
confidence: 91%
“…8(b) we present the performance of two longer codes, Margulis (2640, 1320) code and PEG (1008, 504) code, both (3, 6)-regular LDPC codes. Although the dominant trapping sets are not the same for these codes [30], for both codes the performance improvement can be observed if L ≥ 20. Allowing larger number of iterations results in additional performance improvement.…”
Section: Simulation Analysis Of the Finite Length Ldpc Codesmentioning
confidence: 91%
“…In this paper we also use a term of closed walk, which is a sequence of adjacent edges without restriction of their single appearance [16]. Cycles and closed walks are denoted as and its neighbors contains b odd-degree check nodes [11], for example see Fig. 2.…”
Section: Code Graph Propertiesmentioning
confidence: 99%
“…2. As was proved [10], [11], the performance of an iteratively decoded LDPC code is limited by the existence of small stopping sets and trapping sets in the graph of the code. Since there are very few check nodes capable of correcting errors within the trapping set, this incorrect information remains "trapped" until the termination of the decoding process.…”
Section: Code Graph Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work on exhaustive search for trapping sets ( [11], [12]) has demonstrated that search for (a, b) trapping sets is practical only when a ≤ 11 and a Tanner graph has no more than 1000 variable nodes. Efficient algorithms to find trapping sets with a dominant contribution to the error floor have been proposed by Karimi and Banihashemi [13]. Although these algorithms can handle trapping set of larger size, they may miss lowweight codewords.…”
Section: Introductionmentioning
confidence: 99%